Ampoule Opening Methods within the Hierarchy of Controls: A Simulation-Based Randomized Trial of Safety, Efficiency, and Usability among Nurses - Zu-Chun Lin; Yi-Min Lee; Yi-Lin Hsieh (Journal of Pharmaceutical Innovation, 2027)

Adaptive strategies of emergent plants to per- and polyfluoroalkyl substances - Chang Gao; Zu-lin Hua; Li Gu (Bioresource Technology, 2026)

A dual mechanical tuning framework for rigid pillared elastic metamaterials: Geometric reconfiguration and controllable prestress - Zu Shao; Tong Cheng; Yi Zhang; Wei Zhong Jiang; Zhu Kun Mi; Xiang Jie Wei; Xin Guo; Wang Lin Xiong; Kai Hao Lin; Chuang Li; Shu Hao Song; Cheng Shen; et al. (Engineering Structures, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

More than food: Community culinary heritage as a source of social recognition and perceived emotional benefits in El Morro, Ecuador - Milton Paredes-Aguirre; Lady Soto-Navarrete; Jose Luis Molestina-Garcia; Lin Zu Aguas; Alejandro Bermello (International Journal of Gastronomy and Food Science, 2026)

Co-contamination of hybrid microplastics and PFOA/GenX alters rhizosphere bacterial–fungal communities and root performance of Eichhornia crassipes - Zu-lin Hua; Zi-wei Chen; Ye-bing Shi; Li Gu (Journal of Hazardous Materials, 2026)

Decades-long distribution of per- and polyfluoroalkyl substances (PFASs) in global surface waters: Spatiotemporal variability and future trends - Zu-lin Hua; Chang Gao; Peng Guo; Xiao-qing Li; Li Gu (Journal of Hazardous Materials, 2026)

Physical morphology of conductive carriers shapes anaerobic biofilm development and methanogenesis - Lu Zhang; Wen He; Zu-xiang Yan; Tong-yi Yang; Lin-zhi Zhai; Xiu-jie Wang; Qian-qian Jia; Ze-chong Guo (Bioresource Technology, 2026)

Effect of subsurface barrier on hydrological and stratigraphic alterations during engineering groundwater control - Xiu-Li Xue; Hao-Ying Lin; Chao-Feng Zeng; Gang Zheng; Zu-Hao Zhang; Lei Han; You-Wu Zhao (Journal of Hydrology, 2026)

Polyacrylamide based hydrogel with high temperature and salinity tolerance: the role of aminated distilled spent grain - Xue-Li Long; Kang-Lin Chen; Hong-Ke Yang; Hong-Li Dong; Hong-Kui He; Li-Chun Dai; Zu-Guo Yang; Zhi-Xiang Xu (Biomass and Bioenergy, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Engineering a siderophore-macrolide conjugate via Trojan horse strategy for targeting Pseudomonas aeruginosa and related resistant pathogens - Chun-Yan Zhang; Wei-Min Chen; Guo-Bin Yang; Jing-Hua Wei; Zu-Ju Liang; Xi-Bing Hu; Ping Lan; Jing Lin; Jun Liu (Chemical Engineering Journal, 2026)

Submerge-emerge alternation regulates per(poly)fluoroalkyl substance fate in emergent plants: Insights from growth, physiology, and metabolomics - Ye-bing Shi; Zu-lin Hua; Zi-wei Chen; Xiao-qing Li; Li Gu (Aquatic Toxicology, 2026)

Applying Interpretable Machine Learning for Hypoxia Mitigation: an Operational Framework Coupling Predictive Modeling and Causal Inference for Urban River Management - Jia-yun Chen; Da-wei Wang; Zu-lin Hua; Ke-jian Chu; Li Gu (Water Resources Management, 2026)

Whether the hybridization of polystyrene, polyethylene, and polypropylene microplastics impacts aquatic carbon leakage from water hyacinth: A case study considering per(poly)fluorocarboxylicacid cocontamination - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Chun Wang (Journal of Environmental Chemical Engineering, 2025)

Impact of long-term submerge-emerge alternation on the fate of per- and polyfluoroalkyl substances (PFASs) in sediment-water systems: Insight from dissolved organic matter - Ye-bing Shi; Zu-lin Hua; Zi-wei Chen (Environmental Pollution, 2025)

Chitosan-based Janus dressing with asymmetric wettability for rapid hemostasis, antibacterial protection, and tissue regeneration in hemorrhagic wound management - Jiyuan Wang; Haowen Ye; Kaitong He; Weikang Jiang; Wei Lan; Zu’an Zeng; Peiran Lin; Han Wang; Botao Gao; Wenlong Wang; Yadong Tang (Carbohydrate Polymers, 2025)

The emerging threat of hybrid microplastics: Impacts on per(poly)fluoroalkyl substance bioaccumulation and phytotoxicity in floating macrophytes - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Fu-zhu Ye; Jia-yun Chen; Peng Guo (Journal of Hazardous Materials, 2025)

One-pot synthesis of highly stable CsPbBr₃@C6H7NO3S composite and its application in nitrite fluorescent sensing - Yongzhen Qiu; Yexin Zu; Yating Zhang; Yue Lin; Fang Luo; Zuquan Weng; Cuiying Lin; Jian Wang; Bin Qiu; Zhenyu Lin (Food Chemistry, 2025)

Ultra-stretchable, tough, transparent dermis matrix gel sensors integrated with GCQDs and WO3NPs for visual UVI detection and real-time human motion/temperature sensing - Jialu Shen; Pengtao Zu; Jinwei Zhang; Wei Lin; Haibin Gu (Chemical Engineering Journal, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Low temperature hydrochar from sewage sludge enhancing polyacrylamide-based preformed particle gels with high temperature and salinity tolerance - Bei-Bei Wu; Yan-Yan Xu; Fan Gao; Ya-Jun Wu; Lin-Hui Xi; Zhi Kang; Hong-Kui He; Zu-Guo Yang; Zhi-Xiang Xu (Journal of Water Process Engineering, 2025)

Response of the rhizosphere microenvironment to per(poly)fluoroalkyl substance partitioning induced by submerge-emerge alternation - Ye-bing Shi; Zu-lin Hua; Zi-wei Chen (Journal of Environmental Management, 2025)

Anisotropic deposition of Cu2(OH)3Cl: The critical role of enclosed pit formation heterogeneity - Qihao Lin; Guoqing Chen; Shiwen Zou; Wenlong Zhou; Yufei Zu; Xuesong Fu (Chemical Engineering Journal, 2025)

Design of impact ultrasonic penetrator and optimization of impact efficiency - Yinchao Wang; Ziming Yu; Zihao Yin; Weiwei Zhang; Lin Zu; Guanghong Tao; Suyang Yu (Advances in Space Research, 2025)

Multiphysics simulation of frost heave in unsaturated road systems under covering effect - Lin Li; Zepeng Zhang; Weiling Zu; Panpan Li; Weibing Gong (Transportation Geotechnics, 2025)

Effects of mixed exposure to PFAS on adolescent non-alcoholic fatty liver disease: Integrating evidence from human cohorts, toxicogenomics, and animal models to uncover mechanisms and potential target sites - Xiushuai Du; Dan-Lin Li; Xueming Xu; Yitian Wu; Zhiyuan Du; Gang Liang; Yue-Zu Li; Ya-Jie Zheng; Yu Qin; Kelei Qian; Jing Xu; Liping Gao; et al. (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Insights into the effects of river network topology on sudden pollution risks - Yue-yang Dong; Zu-lin Hua; Peng Wang; Yi-xin Ma (Journal of Hydrology, 2025)

Submerge-emerge alternation promotes sediment per- and polyfluoroalkyl substance (PFAS) release and bioaccumulation - Ye-bing Shi; Zu-lin Hua; Xiao-qing Li; Song-he Zhang; Jian-long Liu (Science of The Total Environment, 2024)

Phosphorus deficiency promotes root:shoot ratio and carbon accumulation via modulating sucrose utilization in maize - Zu-Dong Xiao; Zhen-Yuan Chen; Yi-Hsuan Lin; Xiao-Gui Liang; Xin Wang; Shou-Bing Huang; Sebastian Munz; Simone Graeff-Hönninger; Si Shen; Shun-Li Zhou (Journal of Plant Physiology, 2024)

Application of an α-galactosidase from Bacteroides fragilis on structural analysis of raffinose family oligosaccharides - Heyang Zu; Xuecui Yan; Jing Wu; Jingying Zhao; Kevin H. Mayo; Yifa Zhou; Liangnan Cui; Hairong Cheng; Lin Sun (Carbohydrate Polymers, 2024)

Characteristics of organic matter driven by Eichhornia crassipes during co-contamination with per(poly)fluoroalkyl substances (PFASs) and microplastics (MPs) - Zi-wei Chen; Zu-lin Hua (Science of The Total Environment, 2024)

Human activities exacerbate river network degrading in the Qinhuai River basin - Yue-yang Dong; Peng Wang; Zu-lin Hua; Shan-heng Huang (Science of The Total Environment, 2024)

Eco-environmental responses of Eichhornia crassipes rhizobacteria community to co-stress of per(poly)fluoroalkyl substances and microplastics - Zi-Wei Chen; Zu-Lin Hua (Aquatic Toxicology, 2024)

Malachite green and related substances in environmental samples: Updates on pretreatment and analysis methods - Zu-Yi Chen; Bing-lin He; Yu Bian; Yuan Zhang; Xue-song Feng (Journal of Environmental Chemical Engineering, 2024)

Mass transfer enhancement for simultaneous desulfurization and denitrification by a venturi reactor - Mingfu Zu; Mingqi Lin; Ren Huang; Bobing Tian; Chao Xiao (Journal of Environmental Chemical Engineering, 2024)

Recent advances in micro/nano-robots for environmental pollutant removal: Mechanism, application, and prospect - Jia-yi Hou; Hong-tao Liu; Li-ting Huang; Shu-biao Wu; Zu-lin Zhang (Chemical Engineering Journal, 2024)

Construction of negative electrostatic sugared gourd pore within nickel-based metal-organic framework for one-step purification acetylene from ethylene and carbon dioxide mixture - Xing-Zhe Guo; Bing Lin; Guang-Zu Xiong; Rajamani Krishna; Zhao-Rong Zhang; Qing-Zan Liu; Zhi-Xiong Zhang; Liming Fan; Jie Zhang; Bingwen Li (Chemical Engineering Journal, 2024)

Effect of Co-exposure to Additional Substances on the Bioconcentration of Per(poly)fluoroalkyl Substances: A Meta-Analysis Based on Hydroponic Experimental Evidence - Zi-wei Chen; Zu-lin Hua (Archives of Environmental Contamination and Toxicology, 2024)

Win-win integration: A mitochondria targeted AIE photosensitizer for hypochlorite detection and type I & type II photodynamic therapy - Jiahao Ni; Lichao Yu; Yixuan Wang; Tong Yang; Yueqi Bai; Bowen Zheng; Manshan Liang; Xiaoxia Ye; Yun-Yun Quan; Feifei Lin; Zu-Sheng Huang (Analytica Chimica Acta, 2024)

The bioaccumulation and ecotoxicity of co-exposure of per(poly)fluoroalkyl substances and polystyrene microplastics to Eichhornia crassipes - Zi-wei Chen; Zu-lin Hua; Peng Guo (Water Research, 2024)

Effects of long-chained perfluoroalkyl acids (PFAAs) on the uptake and bioaccumulation of short-chained PFAAs in two free-floating macrophytes: Eichhornia crassipes and Ceratophyllum demersum - Xiao-qing Li; Zu-lin Hua; Jian-yun Zhang; Jun-liang Jin (Journal of Hazardous Materials, 2024)

Improving Ampoule Opening Safety: An Exploratory Comparative Study on an Innovative Ampoule Opener - Zu-Chun Lin; Ming-Chuan Kuo; Hao-Wen Chang; Malcolm Koo (Journal of Pharmaceutical Innovation, 2024)

Molten salt synthesis of MXene-derived hierarchical titanate for effective strontium removal - Siyi Wang; Pengcheng Zhang; Enzhao Ma; Suwen Chen; Zijie Li; Liyong Yuan; Jianhua Zu; Lin Wang; Weiqun Shi (Journal of Hazardous Materials, 2024)

River networks evolution under multiple stresses: A geometric and structural fractal perspective - Yue-yang Dong; Peng Wang; Zu-lin Hua; Xiao-dong Liu (Journal of Cleaner Production, 2024)

Global multifaceted biodiversity patterns, centers, and conservation needs in angiosperms - Ao Luo; Yaoqi Li; Nawal Shrestha; Xiaoting Xu; Xiangyan Su; Yichao Li; Tong Lyu; Kilara Waris; Zhiyao Tang; Xiaojuan Liu; Luxiang Lin; Yongsheng Chen; et al. (Science China Life Sciences, 2024)

Mirror QCD phase transition as the origin of the nanohertz Stochastic Gravitational-Wave Background - Lei Zu; Chi Zhang; Yao-Yu Li; Yuchao Gu; Yue-Lin Sming Tsai; Yi-Zhong Fan (Science Bulletin, 2024)

Novel perspective on qualitative assessment of swine manure compost maturity using organic carbon density fractions - Jia-yi Hou; Hong-tao Liu; Li-xia Wang; Zu-lin Zhang (Bioresource Technology, 2024)

Pelagibacterium flavum sp. nov., Isolated from Soil Sample - Xue-Mei Chen; Zu-Zhen Yang; Si-Rong He; Lian-Shuang Xiong; Qing Yuan; Shu-Ya Zuo; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2024)

Characteristics and triggering mechanisms of early negative Indian Ocean Dipole - Yue Fang; Shuangwen Sun; Yongcan Zu; Jianhu Wang; Lin Feng (Acta Oceanologica Sinica, 2024)

Construction of and evaluation of the immune response to two recombinant pseudorabies viruses expressing the B119L and EP364R proteins of African swine fever virus - Xin-Mei Geng; Ying-Mu Xi; Xiang-Mei Huang; Yang-Lin Wang; Xu-Ying Wang; Kang Ouyang; Ying Chen; Zu-Zhang Wei; Yi-Feng Qin; Wei-Jian Huang (Archives of Virology, 2024)

Somatic embryo induction and plantlet regeneration of Canna × generalis from immature zygotic embryo - Zu-yan Gan; Mu-lin Shu; Feng Yang; Guo-fang Wang; Wen-e Zhang; Xue-jun Pan (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Repairable, reprocessable and recyclable rigid silicone material enabled by dual dynamic covalent bonds crosslinking side-chain - Haoyu Deng; Juan Ye; Zhaoji Zu; Ziqian Lin; Haiqing Huang; Lanyue Zhang; Xiaoji Ye; Hongping Xiang (Chemical Engineering Journal, 2023)

Exogenous Methylglyoxal Ameliorates Source Strength and Retrieves Yield Loss Under Drought Stress During Grain Filling in Maize - Yi-Hsuan Lin; Yu-Ka Jin; Zhen-Yuan Chen; Zu-Dong Xiao; Si Shen; Shun-Li Zhou (Journal of Plant Growth Regulation, 2023)

Nitrogen addition enhanced Per-fluoroalkyl substances’ microbial availability in a wheat soil ecosystem - Jian-yi Wu; Zhi-wei Shen; Zu-lin Hua; Li Gu (Chemosphere, 2023)

Quantitative analysis of the structural evolution in Si anode via multi-scale image reconstruction - Chen Zhu; Shiming Chen; Ke Li; Zu-Wei Yin; Yinguo Xiao; Hai Lin; Feng Pan; Luyi Yang (Science Bulletin, 2023)

Impacts of iron amendments and per-fluoroalkyl substances’ bio-availability to the soil microbiome in wheat ecosystem - Jian-yi Wu; Zu-lin Hua; Zhong-yan Liang; Li Gu (Chemosphere, 2023)

Perfluoroalkyl acids in the aquatic environment of a fluorine industry-impacted region: Spatiotemporal distribution, partition behavior, source, and risk assessment - Zu-lin Hua; Chang Gao; Jian-yun Zhang; Xiao-qing Li (Science of The Total Environment, 2023)

Construction of anodic electron transfer chain based on CuCl2/TiOSO4 synergetic mediators for highly efficient conversion of biomass wastes into electricity at low temperature - Chenxing She; Xihong Zu; Zhiheng Yang; Liheng Chen; Zixin Xie; Hao Yang; Dongjie Yang; Guobin Yi; Yanlin Qin; Xuliang Lin; Wenli Zhang; Huafeng Dong; et al. (Chemical Engineering Journal, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Pyroptosis in inflammation-related respiratory disease - Yuanyu Feng; Min Li; Xiaoting Yangzhong; Xifeng Zhang; Anju Zu; Yunjiao Hou; Lin Li; Shibo Sun (Journal of Physiology and Biochemistry, 2022)
Pyroptosis is commonly induced by the gasdermin (GSDM) family and is accompanied by the release of inflammatory cytokines such as IL-1β and IL-18. Recently, increasing evidence suggests that pyroptosis plays a role in respiratory diseases. This review aimed to summarize the roles and mechanisms of pyroptosis in inflammation-related respiratory diseases. There are several pathways involved in pyroptosis, such as the canonical inflammasome-induced pathway, non-canonical inflammasome-induced pathway, caspase-1/3/6/7/GSDMB pathway, caspase-8/GSDMC pathway, caspase-8/GSDMD pathway, and caspase-3/GSEME pathway. Pyroptosis may be involved in asthma, chronic obstructive pulmonary disease (COPD), lung cancer, acute lung injury (ALI), silicosis, pulmonary hypertension (PH), and tuberculosis (TB), in which the NLRP3 inflammasome-induced pathway is mostly highlighted. Pyroptosis contributes to the deterioration of asthma, COPD, ALI, silicosis, and PH. In addition, pyroptosis has dual effects on lung cancer and TB. Additionally, whether pyroptosis participates in cystic fibrosis (CF) and sarcoidosis or not is largely unknown, though the activation of NLRP3 inflammasome is found in CF and sarcoidosis. In conclusion, pyroptosis may play a role in inflammation-related respiratory diseases, providing new therapeutic targets.

Oncogenic GBX2 promotes the malignant behaviors of bladder cancer cells by binding to the ITGA5 promoter and activating its transcription - Yaoyao Xiong; Xiaohang Song; Kudusi; Xiongbing Zu; Minfeng Chen; Wei He; Lin Qi (Functional & Integrative Genomics, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

Effects of thermal treatment on the macroscopic physical properties and microstructure of Beishan fine-grained granite - Zu-Xi Liu; Yun Wu; Xiao-Zhao Li; Zhen Huang; Jian Lin; Xiao-Hua Pan (Bulletin of Engineering Geology and the Environment, 2022)

Modulation of observed sea surface temperature variation by the quasi‐biweekly oscillation in the tropical western Pacific during boreal summer - Yang Yang; Kuiping Li; Weidong Yu; Yongcan Zu; Lin Liu (International Journal of Climatology, 2022)
Using 17‐year in situ buoy observations, this study investigates how sea surface temperature (SST) over the tropical western Pacific Ocean is modulated by the quasi‐biweekly oscillation (QBWO) during boreal summer. The 10‐buoy mean phase‐by‐phase composites of SST indicate that SST evolution lags behind the convection cycle by approximately one quarter, with the maximum SST occurring in Phase −90° (29.68°C) and the minimum SST occurring in Phase 90° (29.37°C). The diurnal cycle of SST (dSST) is in phase with the convection cycle, with the minimum dSST occurring during the convectively active phase (0.34°C) and the maximum dSST occurring during the convectively suppressed phase (0.61°C). The fluctuation in the dSST reaches 0.27°C, which is similar to that in the SST (0.31°C). This kind of oscillation can be well explained by the evolution of the sea surface forcing parameters, especially the shortwave radiation and wind speeds, observed from the buoys. In addition, the composite range of the dSST suggests an interesting asymmetry between Phase −90° and 90°. The interaction of the background summer mean state and the 10–30‐day intraseasonal anomalies causes the asymmetry in wind speed between Phase −90° and 90°, which in turn results in the asymmetry in the dSST between these two phases. Since QBWOs are more likely to occur during El Niño developing summers than during El Niño decaying summers, the 10–30‐day intraseasonal SST and dSST variances during El Niño developing summers are stronger than those during El Niño decaying summers.

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

Decadal variation of thermocline-sea surface temperature feedback in the tropical Indian Ocean and the underlying mechanisms - Meiqi Zhang; Shuangwen Sun; Lin Liu; Yongcan Zu; Lin Feng (Acta Oceanologica Sinica, 2021)

Synthesis and biological evaluation of novel 1,3-diphenylurea quinoxaline derivatives as potent anticancer agents - Gui-Zhen Li; Xi-Lin Ouyang; Zu-Yu Mo; Yao Gu; Xiao-Lin Cao; Li Yang; Hai-Tao Tang; Ying-Ming Pan (Medicinal Chemistry Research, 2021)

Strong in vitro and in vivo cytotoxic effects of two platinum(II) complexes with cryptolepine derivatives - Li-Qin Qin; Zu-Zhuang Wei; Lin Yang; Qi-Pin Qin; Jia-Jing Zeng; Ming-Xiong Tan; Hong Liang (Medicinal Chemistry Research, 2021)

Comparative transcript profiling and cytological observation of the newly bred recessive genic male sterility non-heading Chinese cabbage (Brassica rapa ssp. chinensis) line WS24-3A - Liping Song; Xia Li; Feng Zu; Changbin Gao; Bincai Wang; Chufa Lin; Jinxing Tu; Aihua Wang; Guolin Zhou (Genes & Genomics, 2019)

Potassium ameliorates iron deficiency by facilitating the remobilization of iron from root cell walls and promoting its translocation from roots to shoots - Yi Quan Ye; Hong Yan Luo; Mao Li; Jia Jun Zhang; Guang Qiu Cao; Kai Min Lin; Si Zu Lin; Shan Shan Xu (Plant and Soil, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Phylogeographic analysis of porcine reproductive and respiratory syndrome virus 1 in Guangdong province, Southern China - Shao-Lun Zhai; Tao Lin; Xia Zhou; Zhang-Fu Pei; Zu-Zhang Wei; He Zhang; Xiao-Hui Wen; Qin-Ling Chen; Dian-Hong Lv; Wen-Kang Wei (Archives of Virology, 2018)

Variations of Laohugou Glacier No. 12 in the western Qilian Mountains, China, from 1957 to 2015 - Yu-shuo Liu; Xiang Qin; Ji-zu Chen; Zhen-lin Li; Jing Wang; Wen-tao Du; Wan-qin Guo (Journal of Mountain Science, 2018)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Investigation of relationships between meteorological conditions and high PM10 pollution in a megacity in the western Yangtze River Delta, China - Yaqun Zu; Lin Huang; Jianlin Hu; Zhan Zhao; Hang Liu; Hongliang Zhang; Qi Ying; Mindong Chen (Air Quality, Atmosphere & Health, 2017)

Identification of a nuclear-recessive gene locus for male sterility on A2 chromosome using the Brassica 60 K SNP array in non-heading Chinese cabbage - Xia Li; Aihua Wang; Feng Zu; Zhenhua Hu; Jiazao Lin; Guolin Zhou; Jinxing Tu (Genes & Genomics, 2016)

Cadmium impairs iron homeostasis in Arabidopsis thaliana by increasing the polysaccharide contents and the iron-binding capacity of root cell walls - Shan Shan Xu; Si Zu Lin; Zhong Xiong Lai (Plant and Soil, 2015)

Ethylene increases accumulation of compatible solutes and decreases oxidative stress to improve plant tolerance to water stress in Arabidopsis - Mengying Cui; Yingchao Lin; Yuangang Zu; Thomas Efferth; Dewen Li; Zhonghua Tang (Journal of Plant Biology, 2015)

Cell-density-dependent manifestation of partial characteristics for neuronal precursors in a newly established human gliosarcoma cell line - Pei-Sen Yao; De-Zhi Kang; Xing-Fu Wang; Ru-Ying Lin; Zu-Cheng Ye (In Vitro Cellular & Developmental Biology - Animal, 2015)

Identification and validation of suitable reference genes for RT-qPCR analysis in mouse testis development - Zu-Kang Gong; Shuang-Jie Wang; Yong-Qi Huang; Rui-Qiang Zhao; Qi-Fang Zhu; Wen-Zhen Lin (Molecular Genetics and Genomics, 2014)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

A role for Ethylene-Insensitive3 in the regulation of hydrogen peroxide production during seed germination under high salinity in Arabidopsis - Yingchao Lin; Lei Yang; Dandan Chen; Yuangang Zu; Zhonghua Tang (Acta Physiologiae Plantarum, 2013)

Loss-of-function mutation of EIN2 in Arabidopsis exaggerates oxidative stress induced by salinity - Yingchao Lin; Dandan Chen; Matthew Paul; Yuangang Zu; Zhonghua Tang (Acta Physiologiae Plantarum, 2013)

Complete genome sequence of narcissus late season yellows virus infecting Chinese narcissus in China - Shuang-Qing Lin; Jian-Guo Shen; Fang-Luan Gao; Wei Cai; Zhen Huang; Li-Yan Xie; Zu-Jian Wu (Archives of Virology, 2012)

Ethylene antagonizes the inhibition of germination in Arabidopsis induced by salinity by modulating the concentration of hydrogen peroxide - Yingchao Lin; Jiajia Wang; Yuangang Zu; Zhonghua Tang (Acta Physiologiae Plantarum, 2012)

Thermal infrared anomalies as a precursor of strong earthquakes in the distant future - Qing-Lin Yao; Zu-Ji Qiang (Natural Hazards, 2012)

Effect of Different Iodine Nutrition on Cerebellum Pcp-2 in Rat Offspring During Lactation - Lu Zhang; Yi Na Sun; Yong Mei Li; Lai Xiang Lin; Yan Ye; Yu Qin Yan; Zu Pei Chen (Biological Trace Element Research, 2011)

The elliptic stress thermal field prior to M S 7.3 Yutian, and M S 8.0 Wenchuan earthquakes in China in 2008 - Qing-Lin Yao; Zu-Ji Qiang (Natural Hazards, 2010)

Shear-wave splitting in the southeast of Cathaysia block, South China - Yuan Gao; Jing Wu; Jin-An Cai; Yu-Tao Shi; Shu Lin; Ting Bao; Zu-Ning Li (Journal of Seismology, 2009)

Characterization of the Mechanism of the Staphylococcus aureus Cell Envelope by Bacitracin and Bacitracin-Metal Ions - Zu-De Qi; Yi Lin; Bo Zhou; Xiao-Di Ren; Dai-Wen Pang; Yi Liu (The Journal of Membrane Biology, 2008)

Laminins in Peripheral Nerve Development and Muscular Dystrophy - Wei-Ming Yu; Huaxu Yu; Zu-Lin Chen (Molecular Neurobiology, 2007)

Auditory response characteristics of the piebald odorous frog and their implications - Zu-Lin Yu; Qiang Qiu; Zhi-Min Xu; Jun-Xian Shen (Journal of Comparative Physiology A, 2006)

The paleogeographic implications of loess mounds: Laizhou Bay plain - Zhang Zu-lu; Liu En-feng; Nie Xiao-hong; Wang Lin (Journal of Geographical Sciences, 2002)

The balance between supply and demand of water resources and the water-saving potential for agriculture in the Hexi Corridor - Qian-zhao Gao; Hu-lin Du; Rui-ping Zu (Chinese Geographical Science, 2002)

The Heterogeneity in Risk Factors of Lung Cancer and the Difference of Histologic Distribution between Genders in Taiwan - Chien-Hung Lee; Ying-Chin Ko; Li Shu-Chuan Cheng; Ying-Chao Lin; Hsiang-Ju Lin; Ming-Shyan Huang; Jhi-Juh Huang; Eing-Long Kao; Hwei-Zu Wang (Cancer Causes & Control, 2001)